PENGARUH PROMOSI, CITRA MERK DAN PELAYANAN TERHADAP MINAT BELI KONSUMEN DI AMELIA BAKERY KOTA BENGKULU - Sulistia, Nia; Pribowo, Muhammad Galy Njoman Ari (UM. Bengkulu, 2024)
This research aims to determine the influence of promotion, brand image and service on consumer buying interest at Amelia Bakery, Bengkulu City, partially and simultaneously. There are several independent variables (X) that will be discussed in this research, including Promotion, Brand Image, and service with the dependent variable (Y) namely Consumer Purchase Interest. The population in this research is all consumers of Amelia Bakery, Bengkulu City. This research used an incidental sampling technique with a total of 90 respondents. The data analysis techniques used are multiple linear regression, coefficient of determination, and hypothesis testing. The data that has been processed is analyzed using the SPSS 25 formula. Based on the research results, there is an influence of promotion (X1) on buying interest (Y) of Amelia Bakery Bengkulu with a sig value of 0.004 < 0.05 and tcount> ttable (4.185>0.135) thus Ho is rejected and Ha is accepted. From the significance value obtained, the variable X1 influences buying interest (Y). There is an influence of brand image (X2) on buying interest (Y) of Amelia Bakery Bengkulu with a sig value of 0.005 < 0.05 and tcount> ttable (5.786>0.135), thus Ho is rejected and Ha is accepted. From the significance value obtained, the variable X2 influences buying interest (Y). There is an influence of promotion (X3) on buying interest (Y) of Amelia Bakery Bengkulu with a sig value of 0.000<0.05 and tcount>ttable (3.701>0.135), thus Ho is rejected and Ha is accepted. From the significance value obtained, the variable X3 influences buying interest (Y). So it is found that promotion, brand image and service together influence purchasing interest with a Fcount value of 9.867 > Ftable 2.65, so it can be concluded that together the independent variables influence the dependent variable. Keywords: Promotion, Brand Image, Service, and Purchase Interest